Conserved but not critical: Trafficking and function of NaV1.7 are independent of highly conserved polybasic motifs - Tyagi, Sidharth; Sarveswaran, Nivedita; Higerd-Rusli, Grant P.; Liu, Shujun; Dib-Hajj, Fadia B.; Waxman, Stephen G.; Dib-Hajj, Sulayman D. (Frontiers in Molecular Neuroscience, 2023)
Non-addictive treatment of chronic pain represents a major unmet clinical need. Peripheral voltage-gated sodium (NaV) channels are an attractive target for pain therapy because they initiate and propagate action potentials in primary afferents that detect and transduce noxious stimuli. NaV1.7 sets the gain on peripheral pain-signaling neurons and is the best validated peripheral ion channel involved in human pain, and previous work has shown that it is transported in vesicles in sensory axons which also carry Rab6a, a small GTPase known to be involved in vesicular packaging and axonal transport. Understanding the mechanism of the association between Rab6a and NaV1.7 could inform therapeutic modalities to decrease trafficking of NaV1.7 to the distal axonal membrane. Polybasic motifs (PBM) have been shown to regulate Rab-protein interactions in a variety of contexts. In this study, we explored whether two PBMs in the cytoplasmic loop that joins domains I and II of human NaV1.7 were responsible for association with Rab6a and regulate axonal trafficking of the channel. Using site-directed mutagenesis we generated NaV1.7 constructs with alanine substitutions in the two PBMs. Voltage-clamp recordings showed that the constructs retain wild-type like gating properties. Optical Pulse-chase Axonal Long-distance (OPAL) imaging in live sensory axons shows that mutations of these PBMs do not affect co-trafficking of Rab6a and NaV1.7, or the accumulation of the channel at the distal axonal surface. Thus, these polybasic motifs are not required for interaction of NaV1.7 with the Rab6a GTPase, or for trafficking of the channel to the plasma membrane.